Cross entropy weight minimization of a compressive strut - Micu, L. Alexandru (2016)
In this study, a population-based optimization algorithm is used to minimize the weight of a compressive strut. A geometrically nonlinear analysis is carried out to get an accurate measure of the structure’s true capacity, allowing for individual member and overall structure (and sub-structure) buckling. To overcome the computational challenge of nonlinear analysis, the study uses a simple definition of the onset of instability and hence the number of iterations is cut to a minimum.